INFLUENCE OF SUPPLEMENTATION OF COPPER AT TWO LEVELS AND FLAVOMYCIN ON THE MINERAL CONCENTRATIONS IN PLASMA AND TIBIA OF BROILER CHICKEN - Vasanth, S; Dipu, MT; Shyama, K; Ponnuvel, P (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
To determine the influence of copper (Cu) supplementation at two dietary levels and flavomycin on the mineral concentrations in plasma and tibia, a feeding experiment was carried out with 160 day old broiler chicks (VenCobb 400) for a period of 42 days. The birds were divided into four treatment groups (T1 to T4) with four replicates of ten chicks in each. Statistical analysis revealed significant (P<0.01) difference in plasma Ca, P, Cu and, Fe concentrations among the treatment groups T1, T2, T3 and T4. The result indicates that the supplementation of either copper or flavomycin had a positive influence on the mineral concentrations of both plasma and tibia in broilers.